Clinical association of vitamin D and serotonin levels among patients with fibromyalgia syndrome - Amin OA (Dove Medical Press, 2019)
Omar A Amin,1 Saleh M Abouzeid,2 Siham A Ali,3 Bashir A Amin,4 Khaled A Alswat51Department of Orthopedic, Al Noor Specialist Hospital, Makkah, Saudi Arabia; 2Department of Rheumatology, Al Azhar University, Cairo, Egypt; 3Department of Neurology, Banha University, Banha, Egypt; 4Department of Medicine, Taif University, School of Medicine, Taif, Saudi Arabia; 5Department of Medicine and Endocrinology, Taif University School of Medicine, Taif, Saudi ArabiaObjective: Fibromyalgia syndrome (FMS) is a chronic disorder associated with severe pain. According to the National Fibromyalgia Association, the prevalence of FMS is between 3% and 6% in the general population, with about 90% of the patients being women. The primary goal of this study was to evaluate the relationship between vitamin D and serotonin levels and FMS severity.Methods: Forty participants with fibromyalgia (mean age: 37.8±9.5 years) were included and had their medical history taken, a physical examination, and laboratory testing in the Rheumatology Department at Al-Ameen Hospital in Taif, Saudi Arabia. The revised Fibromyalgia Impact Questionnaire (FIQR) was used to determine the FMS severity.Results: The results showed that 42.5% of the patients were considered to have mild/moderate fibromyalgia, with the remainder having severe/extreme fibromyalgia. The latter were more likely to have lower serotonin levels. The results showed a significant dose-dependent negative relationship between the serotonin levels and FIQR scores (P=0.002). However, no significant correlations were found between the vitamin D levels and FIQR scores (P=0.112).Conclusion: The findings of this study show that the improved health of FMS patients is associated with normal serotonin levels.Keywords: fibromyalgia, vitamin D, serotonin, Saudi Arabia, Taif